The Mean Streets of the Global Village: Crimes of Exclusion in the United States and Darfur - Hagan, John (Journal of Scandinavian studies in criminology and crime prevention, 2007)
This paper considers similarities as well as differences in state-based systems of selective exclusion found in the United States and Sudan. Albeit in different ways and to different degrees, large numbers of homeless adults and children are denied the basic human right to secure shelter in the nations of both the Global North and the Global South. Homelessness and imprisonment are pervasive forms of social exclusion in the late modern Global North, while forced migration and mortality are persistent forms of social exclusion in the contemporary Global South. The domestic policies of exclusion in the North-with their legalized use of arrest, due process, conviction, incarceration and homelessness-are a world apart from the policies of criminal exclusion in the Global South-with their death squads, militias, disappearances and displacements. Yet both depend on repression rather than restoration. Mass incarceration and genocidal death and displacement display an awkward symmetry along the mean streets of the global village, and the fragile and disrupted families of the North parallel the destroyed and displaced families of the South. They are parallel faces of vulnerability. The mean streets of the United States and Sudan are not the same, but their risks and vulnerabilities involve parallel and failed policies of punishment, repression, and exclusion